THE INFLUENCE OF FINANCIAL REPORTING PRESENTATION, INTERNAL CONTROL, ACCOUNTABILITY, AND HUMAN RESOURCE COMPETENCY ON THE IMPLEMENTATION OF FINANCIAL REPORTING TRANSPARENCY IN THE INDRAGIRI HILIR REGIONAL GOVERNMENT - Siti Aisyah; Suryani, Suryani; Badewin, Badewin (Indragiri Research Center (ingreat), 2023)
The Influence of Financial Report Presentation, Internal Control, Accountability, and Human Resource Competency on the Implementation of Financial Reporting Transparency in the Regional Government of Indragiri Hilir Regency. This research aims to determine the influence of the presentation of Financial Reports, Internal Control, Accountability and Human Resource Competence on the implementation of Transparency in Financial Reporting of the Regional Government of Indragiri Hilir Regency. This research was conducted at the OPD in Indragiri Hilir Regency. The population in this study were all finance department employeesin a OPD Companyin the Regency Indragiri Hilir. The sampling technique used a purposive sampling method, so that a sample of 69 people from 33 OPDs was obtained. The analysis technique used is Multiple Regression Analysis. Test results show that the presentation of financial reports influences the implementation of financial reporting transparency in the regional government of Indragiri Hilir Regency, internal control influences the implementation of financial reporting transparency in the regional government of Indragiri Hilir district, accountability influences the implementation of financial reporting transparency in the regional government of Indragiri Hilir Regency, and resource competency. Humans Simultaneously Influence the Implementation of Transparency in Financial Reporting of the Regional Government of Indragiri Hilir Regency.